Flesh flies (Diptera: Sarcophagidae) of Kalamaili Mountain Ungulate Nature Reserve (China: Xinjiang): checklist and description of four new species - Zhang, Ming; Xu, Wen-Tian; Pape, Thomas; Pei, Wen-Ya; Zhang, Dong (Zootaxa, 2021)
A checklist of the flesh flies occurring in Kalamaili Mountain Ungulate Nature Reserve, Xinjiang, NW China, is presented, based on material collected from 2009 to 2017. The checklist includes 18 genera and 46 species, 12 of which are new records for China. Four new species are described: Asiosarcophila kashanensis sp. nov., Miltogramma szpilai sp. nov., Sphecapatodes superciliosa sp. nov., and Sphecapatodes xinjiangensis sp. nov. Extensive documentation of the male and female habitus, details of the head, and the specialised setae of the male fore tarsus is given for all species where relevant, except for those already well illustrated in other publications. The male terminalia of almost all species of Paramacronychiinae and Sarcophaginae recorded from Kalamaili are illustrated with focus-stacked photographs.